2009
DOI: 10.1016/s1472-6483(10)60429-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiling in endometrial secretions: a non-invasive window on endometrial receptivity

Abstract: Investigation of human embryo implantation requires a non-disruptive means of studying the endometrium during the window of implantation. This study describes a novel approach of cytokine profiling in endometrial secretions. Endometrial secretions aspirated prior to embryo transfer from 210 women undergoing IVF or intracytoplasmic sperm injection were analysed by a multiplex immunoassay. Ten mediators [interleukin (IL)-1beta, IL-6, IL-12, IL-18, tumour necrosis factor-alpha, macrophage migration inhibitory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 77 publications
3
106
0
2
Order By: Relevance
“…Interest in the protein content of endometrial secretions has gained much momentum in recent years and has been suggested to play a key role in the embryo implantation process. Therefore, differential proteomics of the eninsight to understand the mechanisms involved in the onset of endometrial pathologies and the process of embryo implantation [2].…”
Section: Communicationmentioning
confidence: 99%
“…Interest in the protein content of endometrial secretions has gained much momentum in recent years and has been suggested to play a key role in the embryo implantation process. Therefore, differential proteomics of the eninsight to understand the mechanisms involved in the onset of endometrial pathologies and the process of embryo implantation [2].…”
Section: Communicationmentioning
confidence: 99%
“…This issue should be addressed based on the analysis to be undertaken. For instance, blood contamination recovered from ALF samples in women was a confounder factor when analysing pro-inflammatory cytokines since red cells interfered with the measurements of pro-inflammatory cytokines in uterine fluid aspirated from women (Boomsma et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Badania takie mogłyby być niezwykle użyteczne przy określaniu optymalnego czasu transferu zarodka do macicy w procedurze IVF, jeszcze w tym samym cyklu, w którym przeprowadzono badanie wydzieliny. Dalsze badania powinny skupić się na wyjaśnieniu zmian poziomu poszczególnych markerów podczas cyklu miesięcznego kobiety, dopuszczalnej zmienności w poziomach markerów pomiędzy cyklami i opracowania zakresu wartości prawidłowych poszczególnych markerów w poszczególnych fazach cyklu [27,28].…”
Section: Opis Stanu Wiedzyunclassified
“…[27] dokonali analizy składu cytokin w wydzielinie macicy oraz śluzu szyjkowego kobiet w okresie receptywności doczesnej. Wśród wykrytych substancji znalazło się wiele czynników o różnych funkcjach i właś-ciwościach, np.…”
Section: Opis Stanu Wiedzyunclassified